FENOMENA BUNUH DIRI DI KABUPATEN GUNUNG KIDUL - Andari, Soetji (Puslitbangkesos Kementerian Sosial RI, 2017)
AbstractThe phenomenon of suicide from mental disorder as the most common causes, symptoms that occur a range of psychiatric conditions of distress. This includes the mental condition of despair, loneliness, anxiety, depression, and it is a lot happening in the Gunungkidul Regency. Descriptive research approach of case study method with the informants specified in purposive sampling, data collection techniques, namely the observation at the site of the suicide incident, interviews with a variety of Government such as police informants related, Office and NGOs are important in the prevention of suicide. The results of the research on the phenomenon of suicide themselves as a human tragedy often occurs in Gunungkidul, perpetrators of the suicide based on gender men more than women. The perpetrators of the most outcome of chronical diseases suicide and depression. Depression is a result of the loss of jobs, insufficient family needs, divorce, infidelity in marriage. While the perpetrators of suicide in older results from chronic illness and loneliness due to the loss of a family member. Almost all of the suicide scene was quiet conditions at home, it can be in the bedroom, bathroom, kitchen means that home is where the most widely as a place to commit suicide. This type of suicide in Gunungkidul tend to egoistik, a person committing suicide because it feels itself a larger importance than social interests. Keywords: Suicide, a phenomenon, the human tragedy